PERFORMANCE ANALYSIS OF UNSIGNALIZED INTERSECTION OF DELAY USING GAP ACCEPTANCE METHOD - Fajrina Aghnia Sya’bani; Andhy Romdani (Jurusan Pendidikan Teknologi Dan Kejuruan, 2026)
Traffic movement problems often occur during peak hours in the morning to evening in Tasikmalaya City, as happened at the intersection of Ahmad Yani Street-Mohammad Hatta Street. The dense traffic flow at the intersection is due to Ahmad Yani Street-Mohammad Hatta Street is a connecting road between Ciamis Regency and Tasikmalaya City, this road is one of the accesses to the center of the economy, offices, to education. The condition of Ahmad Yani Street-Mohammad Hatta Street which is often traversed by large to small vehicles adds to the traffic density on the road. Gap acceptance is a state when the driver feels that he can safely perform the movement of joining the mainstream. While gap rejection is a situation when the driver slows down the speed of his vehicle due to a gap that is too small so he has to wait to be able to join the main stream. From the results of the study for 16 days obtained a critical gap value at the intersection of Ahmad Yani Street-Mohammad Hatta Street amounted to 7.50 seconds and the delay time to the crossing conflict at the intersection of three no signal using the gap acceptance method is equal to 12,37 seconds. Meanwhile, with the Indonesian Road Capacity Guideline Method 2023, a delay value of 10,01 seconds/SMP is obtained.